2016
DOI: 10.1155/2016/8687575
|View full text |Cite
|
Sign up to set email alerts
|

Basic Parameters of Blood Count as Prognostic Factors for Renal Cell Carcinoma

Abstract: Background. Renal cell carcinoma is the most common type of kidney cancer. Taking account of morbidity and mortality increase, it is evident that searching for independent prognostic factors is needed. Aim of the Study. The aim of the study was to analyze routinely performed blood parameters as potential prognostic factors for kidney cancer. Material and Methods. We have retrospectively reviewed the records of 230 patients treated for renal cell carcinoma in the years 2000–2006. Preoperative blood parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Seles et al defined MPV lower than 9.5 fl as a negative prognostic factor for CSS [22]. Prokopowicz et al proposed the MPV cut-off value as 10.1 fl, given that patients with lower values suffered from significantly higher cancer-specific mortality [21]. Yun et al discovered that patients with MPV lower than 7.5 fl had shorter OS [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seles et al defined MPV lower than 9.5 fl as a negative prognostic factor for CSS [22]. Prokopowicz et al proposed the MPV cut-off value as 10.1 fl, given that patients with lower values suffered from significantly higher cancer-specific mortality [21]. Yun et al discovered that patients with MPV lower than 7.5 fl had shorter OS [23].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased MPV was associated with decreased survival in non-small cell lung cancer and esophageal cancer patients [19,20]. In RCC patients, two studies confirmed MPV as an independent prognostic factor for cancer-specific survival (CSS) [21,22] and one study proved it to be an independent prognostic factor of OS [23].…”
Section: Introductionmentioning
confidence: 98%
“…Studies have indicated that the renal cancer patients who have thrombocytosis mostly have unfavourable prognoses after surgery. 21 , 30 , 36 Our study has indicated that a high level of PLT could be a risk factor for the recurrence of renal cancer.…”
Section: Discussionmentioning
confidence: 81%
“…The solution might be found in cheap and easy obtainable blood-based indicators. Different complete blood count (CBC) parameters were reported to have an association with overall survival in RCC, such as neutrophil count, platelet count, neutrophil-to-lymphocyte ratio and mean platelet volume [16][17][18][19][20][21]. These markers are routinely used in everyday practice.…”
Section: Discussionmentioning
confidence: 99%